Obtenção e fracionamento de ésteres metílicos de ácidos graxos a partir do óleo de coco ariri (Syagrus cocoides martius) - BASTOS, Fernanda Carneiro (2020)
Despite the great diversity of palm trees (Arecaceae) there is still no data on many of them, for example ariri. The ariri is of the Syagrus genus and has fruits composed of oily almonds and its application is mainly restricted to popular use. This work aims to evaluate the ariri coconut almond oil, as to the extraction method and as a raw material for obtaining enriched fractions of methyl esters of fatty acids. Initially, the species used was identified. The extraction of almond oil was performed in cold and hot way, with fruits collected in a dry and rainy season; and analyzed as to the yield and physical-chemical parameters.The esters were obtained by alkaline transesterification, under magnetic stirring at 60 ° C (333, 15 F), 1:18 m / m molar ratio (oil: methanol) and 1% KOH catalyst (% oil mass); for 1 hour. The fractionation of the esters was performed by liquid column chromatography, packed with silica gel 60, mobile phase hexane / ethyl acetate; accompanied by Thin Layer Chromatography and Gas Chromatography coupled to Mass Spectrometer. The species was identified as Syagruscocoides Martius. The extractions proved to be efficient and without significant changes due to the method used. As for the collection period, the oil from fruits obtained in the dry period showed better quality. Several fractions were obtained among them pure fraction of the methyl ester of lauric acid and mixtures containing 2-6 esters, with 62.7–96.95% of the methyl ester of lauric acid. This result accredits coconut ariri as an excellent raw material for obtaining new high purity standards and as a raw material for application in various products.